ACOCA-G: scenario-based context query generation for evaluating performance of context management platforms - Ravindi De Silva; Arkady Zaslavsky; Seng W. Loke; Prem Prakash Jayaraman (Discover Internet of Things)
Abstract Context-awareness is a pivotal trend within the Internet of Things research area, facilitating the near real-time processing and interpretation of relevant sensor data to enhance data processing efficiency. Context Management Platforms (CMPs), as advanced IoT middleware platforms offer promising solutions to IoT applications by offering seamless interoperability between different IoT silos. However, significant gaps still remain in evaluating the performance of CMPs, especially the data retrieval aspect of CMPs. Existing IoT middleware evaluation approaches lack flexible, user-friendly approaches to generate query loads to address aforementioned limitation. This paper introduces ACOCA-G (Adaptive COntext CAching-Generator), a configurable automated framework designed to generate scenario-based context queries to evaluate data retrieval of CMPs. ACOCA-G transforms real-world scenarios into scene descriptions in a specified format, which are then converted into Context-aware Scene Graphs (CSGs). ACOCA-G framework introduces a novel situation reasoning approach that integrates concepts of Context Spaces Theory (CST) and enhanced Situation State Machines (SSM). CSG reasoning identifies situations, facilitating the generation of dynamic and context-specific query loads. The framework produces template-based queries of varied complexities, demonstrating ACOCA-G’s flexibility and adaptability in generating queries closely aligning with real-world query complexities. Empirical evaluations using real-world IoT datasets and scenes of diverse complexities assess ACOCA-G in terms of query completeness, volume, and generation efficiency, providing insights into accuracy, scalability, and effectiveness. As a pioneering solution for systematically evaluating CMP performance, ACOCA-G serves as a robust tool for addressing gaps in CMP data retrieval assessment.